Predicting the factors related to cervical cancer screening in secondary school female teachers in Shahrekord: Application of PEN-3 model factors about cervical cancer screening in female teachers - Zahra Karimi; Nasim Mehri Ghahfarokhi; Mina Karimian; Leili Rabiei (Shahrekord University of Medical Sciences, 2022)
Background and aims: Cervical cancer is one of the most common cancers in women. Cervical cancer screening is one of the essential measures for preventing this disease, and its purpose is to detect lesions in the premalignant stage and reduce the risk of death from this cancer. This study aimed to predict the factors related to cervical cancer screening in secondary school teachers using the PEN-3 model in Shahrekord, southwest Iran. Methods: This descriptive-analytical study was conducted on secondary school female teachers in the academic year 2019-2020. The samples were 228 individuals who were selected by convenience random sampling. The research tools were a demographic information checklist, uterine screening performance information, and a questionnaire based on PEN-3 model constructs (perceptual, enabling, and reinforcing factors). Data analysis was done using SPSS version 22. Results: Regarding cervical cancer screening (Pap smear test), 59.82% of the teachers had a history of undergoing Pap smear tests, of which 35.43% had performed the test regularly. Pearson's correlation coefficient showed a direct and significant correlation between PEN-3 model constructs (perceptual, enabling, and reinforcing factors) and a history of cervical cancer screening (P<0.001). In the regression analysis of demographic variables and PEN-3 model constructs, the predictive value of these variables for cervical cancer screening was obtained at 0.57%. Conclusion: Based on the findings of the study and given the role of PEN-3 model constructs (perceptual factors, enabling factors, and reinforcing elements) in predicting cervical cancer screening behavior, comprehensive planning for intervention and use of this educational model and gaining knowledge about the cultural and socioeconomic factors for cervical cancer screening seems useful.